To, In, The, A STRATEGIES TO TACKLE ACADEMIC DISHONESTY IN EFL STUDENTS’ WRITINGS IN THE ERA OF ARTIFICIAL INTELLIGENCE: A QUALITATIVE RESEARCH - Rizki Alysa; Lukman Syahbana (Research on English Language Education, 2025)
The rise of artificial intelligence (AI) has transformed academic writing, especially among English as a Foreign Language (EFL) students. While tools like ChatGPT, QuillBot, and Grammarly support language learning, their misuse has led to increased academic dishonesty. This study investigates how AI contributes to such dishonesty and explores institutional strategies to address it. Using a qualitative descriptive approach through desk research, the study reviews literature from academic sources. Findings show that dishonesty occurs both intentionally and unintentionally, often due to low AI literacy and lack of ethical guidelines. Students tend to overuse AI for paraphrasing, grammar checks, or full-text creation, reducing critical thinking and engagement. In response, institutions are advised to implement AI policies, promote AI literacy, apply process-based assessment, and train lecturers in ethical AI use. These measures aim to uphold academic integrity and ensure AI enhances learning.